(untitled) (Bangladesh Journal of Child Health, 2018)
Background: Pneumonia contributes to between 750,000 and 1.2 million neonatal deaths worldwide annually and neonatal pneumonia accounts for 10% of global child mortality. Chest radiography is the primary and most important imaging modality in the evaluation of neonatal pneumonia. The study was conducted to evaluate the common radiological findings of pneumonia among neonates to early diagnose the disease. Methodology: This prospective observational study was conducted in Dhaka Shishu (children) Hospital from April to September 2014. A total of 50 neonates admitted in the inpatient department were included who fulfilled the inclusion criteria’s like having difficult breathing, fast breathing>60 /min, severe chest indrawing, grunting, cyanosis, cough or fever. Diagnosis was confirmed by Chest X-ray. Positive X-ray findings like lobar or segmental consolidation, nodular or coarse patchy parenchymal infiltrate, diffuse haziness or granularity, air bronchogram were included into the study. X-ray changes were assessed. Results: Most commonly identified abnormality was patchy opacities (included nodular or coarse patchy opacities, diffuse haziness, air bronchogram), noted in 31(62.0%) cases. Followed by homogenous opacities (consolidation) were found in 19(38.0%) cases. Multifocal area involvement were found more 56.0 %(28) than single area. On right side radiological changes commonly noted, especially right upper zone involvement was the commonest 30 (66.0%). A comparison between severe and non- severe cases revealed that both types of opacities were found equally. But right sided Involvement was common in both groups. Conclusion: Multifocal patchy opacities were the most common radiological finding in cases of neonatal pneumonia. Pneumonia lesions were more common in the right lung among neonates and common site was right upper zone. Bangladesh J Child Health 2017; VOL 41 (3) :155-158